Syntheses and photovoltaic properties of 6-(2-thienyl)-4H-thieno[3, 2-b]indole based conjugated polymers containing fluorinated benzothiadiazole. (27th January 2017) - Jeong, Ina; Chae, Sangmin; Yi, Ahra; Kim, Juae; Chun, Ho Hwan; Cho, Jung Hyeong; Kim, Hyo Jung; Suh, Hongsuk
Abstract: In this report, a series of copolymers based on 6-(2-thienyl)-4 H -thieno[3, 2- b ]indole (TTI) as an electron-rich unit and fluorinated DTBT as an electron-deficient unit were synthesized, namelyPTTIF1 andPTTIF2, and applied to photovoltaic devices. TTI unit was coupled with fluorinated DTBT to utilize the merit of introduction of fluorine atom leading to the lowering of the HOMO energy level while keeping high planarity of the conjugated backbone. The synthesized copolymers show a noticeable change in HOMO energy levels as compared with non-fluorinated polymer (PTTIDTBT- h ). Optimized photovoltaic devices ofPTTIF2 exhibited power conversion efficiency of 4.36% with decent J SC and FF values, which can be explained by the higher charge transporting ability ofPTTIF2 with preferable face-on crystallite population thanPTTIF1 in grazing incident wide-angle X-ray scattering (GIWAXS). Graphical abstract: Highlights: The series of 6-(2-Thienyl)-4 H -thieno[3, 2- b ]indole -based polymers were synthesized. The polymers exhibited deep HOMO energy levels due to the strong electron-withdrawing ability of fluorine atom. The optimal device performance reached a power conversion efficiency of 4.36%.